Gambaran Estimasi Laju Filtrasi Glomerulus (eGFR) dan Kreatinin sebagai Indikator Fungsi Ginjal di Yayasan Baptis Cengkareng Indah - Hendrawan, Siufui; Santoso, Alexander Halim; Destra, Edwin; Hartono, Eric; Soeltanong, Dianova; Khoto, Anthon Eka Prayoga (SEWAGATI: Jurnal Pengabdian Masyarakat Indonesia, 2025)
The number of cases of kidney disorders continues to rise, often going unnoticed due to the absence of symptoms in the early stages. Examination of creatinine levels and estimation of glomerular filtration rate (eGFR) can identify impaired kidney function before permanent damage occurs. The habit of drinking enough water is one simple way to maintain kidney function. The activity was carried out using the Plan-Do-Check-Act (PDCA) approach. Officers took venous blood samples aseptically for analysis in the laboratory to assess creatinine levels and calculate eGFR. Participants received the results of the examination along with education about the role of hydration in supporting kidney excretion. The examination involved 62 participants aged 23 to 76 years. The median eGFR value was recorded as 97.0 mL/minute, and creatinine levels ranged from 0.60 to 3.77 mg/dL. Kidney function screening identified participants at risk of decreased excretory capacity. Education about the importance of drinking water regularly needs to be provided to prevent further kidney damage and maintain optimal filtration function.